Fusion of the molecular adjuvant C3d to cleavage-independent native-like HIV-1 Env trimers improves the elicited antibody response - Bale, Shridhar; Yang, Lifei; Alirezaei, Mehrdad; Wilson, Richard; Ota, Takayuki; Doyle, Esmeralda D.; Cottrell, Christopher A.; Guenaga, Javier; Tran, Karen; Li, Wenjuan; Stamatatos, Leonidas; Nemazee, David; et al. (Frontiers in Immunology, 2023)
An effective HIV vaccine likely requires the elicitation of neutralizing antibodies (NAbs) against multiple HIV-1 clades. The recently developed cleavage-independent native flexibly linked (NFL) envelope (Env) trimers exhibit well-ordered conformation and elicit autologous tier 2 NAbs in multiple animal models. Here, we investigated whether the fusion of molecular adjuvant C3d to the Env trimers can improve B cell germinal center (GC) formation and antibody responses. To generate Env-C3d trimers, we performed a glycine-serine based (G4S) flexible peptide linker screening and identified a linker range that allowed native folding. A 30-60 amino acid long linker facilitates Env-to-C3d association and achieves the secretion of well-ordered trimers, structural integrity and functional integrity of Env and C3d. The fusion of C3d did not dramatically affect the antigenicity of the Env trimers and enhanced the ability of the Env trimers to engage and activate B cells in vitro. In mice, the fusion of C3d enhanced germinal center formation, magnitude of Env-specific binding antibodies, and the avidity of the antibodies in the presence adjuvant. The Sigma Adjuvant Systems (SAS) did not affect the trimer integrity in vitro, but contributed to altered immunogenicity in vivo, resulting increased tier 1 neutralization, likely by increased exposure of variable region 3 (V3). Taken together, the results indicate that the fusion of the molecular adjuvant, C3d, to the Env trimers improves antibody responses, and could be useful for Env-based vaccines against HIV.